Molecular genetic characterization analysis of a novel HIV-1 circulating recombinant form (CRF156_0755) in Guangdong, China - Lin, Yaqing; Lan, Xianglong; Xin, Ruolei; Ling, Xuemei; Xiao, Mingfeng; Li, Feng; Hu, Fengyu; Li, Linghua; Lan, Yun (Frontiers in Microbiology, 2024)
Introduction The characteristic of human immunodeficiency virus type 1 (HIV-1) is its susceptibility to erroneous replication and recombination, which plays a crucial role in the diverse and dynamic variation of HIV-1. The spread of different subtypes in the same population often leads to the emergence of circulating recombination forms (CRFs). At present, the main recombinant subtypes of HIV-1 in China are CRF07_BC, CRF01_AE, CRF08_BC and B′ subtypes, while CRF55_01B has become the fifth major epidemic strain in China after rapid growth in recent years since it was first reported in 2013. In this study, we obtained five nearly full-length genomes (NFLGs) and one half-length genome from five different cities in Guangdong. Here, we focused on analyzing their characteristics, parental origin and drug resistance. Methods Plasma samples were collected from six HIV-1 infected patients in Guangdong Province who had no epidemiological association with each other. The NFLGs of HIV-1 were amplified in two overlapping segments by the near-terminal dilution method. The positive products were sequenced directly to obtain genomic sequences. The recombinant patterns and breakpoints of the NFLGs were determined using the Simplot software and confirmed by the maximum likelihood trees for segments using the IQ-TREE and BEAST software. The genotypic resistance profiles of the protease reverse transcriptase and integrase were resolved by the Stanford HIV drug resistance database. Results The six genomes shared highly similar recombinant pattern, with the CRF55_01B backbone substituted by CRF07_BC segments, therefore assigned as CRF156_0755. The evolutionary analysis of the segments showed that CRF07_BC segments were not clustered with the Chinese MSM variants in the CRF07_BC lineage. All the five NFLGs were identified with the non-nucleoside reverse-transcription inhibitors (NNRTIs) resistance mutation V179E. Discussion With the accumulation and evolution of recombination between CRF55_01B and CRF 07_BC, the prevalence of more recombinant strains of CRF55_01B and CRF 07_BC may occur. Therefore, it is necessary to strengthen the identification and monitoring of the recombination of CRF55_01B and CRF 07_BC.